Revision of the ammonite index species Berriasella jacobi Mazenot, 1939 and its consequences for the biostratigraphy of the Berriasian Stage - Frau, Camille; Bulot, Luc G.; Reháková, Daniela; Wimbledon, William A. P.; Ifrim, Christina (Cretaceous research, 2016)
Berriasella jacobi is a key ammonite taxon that has been widely used for the definition of the Tithonian/Berriasian boundary and has been widely quoted in the literature as the index species for the lowest zone of the Berriasian Stage. The taxonomic revision of B. jacobi shows that it should be excluded from the genus Berriasella and transferred to the genus Strambergella. Analysis of the literature has convinced us that most specimens illustrated as B. jacobi have been misidentified. New collection at Le Font de Saint Bertrand (Les Combes, Glandage, Drôme, France) shows us the type series corresponds to the microconch form of a dimorphic pair. New integrated data on its stratigraphic distribution causes us to question its value as an index species for the base of the Berriasian.
Gesehen am 25.05.2020